A Model for Predicting the Risk of Developing Drug-Induced Liver Injury During Therapy with Favipiravir - Yu. V. Shevchuk; I. V. Sychev; A. V. Kryukov; I. I. Temirbulatov; K. B. Mirzaev; N. P. Denisenko; Sh. P. Abdullaev; S. N. Tuchkova; V. I. Vechorko; O. V. Averkov; D. A. Sychev (Антибиотики и Химиотерапия)
Favipiravir is an antiviral drug that has become widely used for the etiotropic treatment of COVID-19. According to a number of studies, the incidence of adverse reactions during favipiravir therapy reaches 93%, and the most common adverse reaction is an increase in the level of liver enzymes in the blood. The aim was to study the influence of gender-age, clinical-anamnestic and pharmacogenetic factors on the development of drug-induced liver injury during favipiravir therapy in hospitalized patients with COVID-19. Material and methods. The study included 150 hospitalized patients with COVID-19 receiving favipiravir therapy. Patients were divided into 2 groups: group 1 — 31 patients who developed an increase in alanine transaminase levels multiple of two upper limits of normal or more against the background of favipiravir therapy; group 2 (control) — 119 patients who did not develop this adverse reaction. A retrospective analysis of case histories was performed in patients of both groups, and a pharmacogenetic study was performed in 14 patients of group 1 and 71 patients of group 2. Based on the data obtained, the association of clinical, laboratory, pharmacological, and pharmacogenetic parameters with the development of drug-induced liver injury during favipiravir therapy was studied. Results. There were significantly more younger individuals in the group of patients who developed drug-induced liver injury than in the control group (60.48±15.93 and 66.38±14.23 years respectively, P=0.047), with a lower level of lymphocytes in the blood (1.103±0.644 and 1.537±1.866 109/l respectively, P=0.022) and a higher level of interleukin-6 (288.019±344.794 and 152.490±274.67 pg/ml respectively, P=0.045), as well as those receiving cephalosporin therapy (OR=4.891, CI=1.610–14.862, 2χ =9.047, P=0.003), beta-blockers (OR=0.416, CI=0.177–0.978, χ²=4.190, P=0.041), diuretics (OR=0.328, CI=0.107–1.006, P=0.043), interleukin inhibitors (OR=4.891, CI=1.610–14.862, χ²=9.047, P=0.003) and those who underwent repeated administration of interleukin inhibitors (OR=6.884, CI=2.609–18.168, χ²=18.048, P=0.000). Conclusions. Younger age, lower lymphocyte counts, and higher interleukin-6 levels in the blood, as well as concomitant therapy with cephalosporins, betablockers, diuretics, and interleukin inhibitors, including repeated administration of interleukin inhibitors, increase the likelihood of developing drug-induced liver injury during favipiravir therapy. Therefore, it is necessary to take these factors into account when prescribing favipiravir therapy, conduct more careful monitoring of clinical and laboratory indicators of liver damage, and develop personalized approaches to the treatment of patients with COVID-19.